Arab dialects that formed the classical Arabic, in which the Holy Qur’an was revealed - Mohd. Shamsuddin, Salahuddin; H. Asmad, Arman Bin; Hj. Ahmad, Siti Sara Binti (Advances in Social Sciences Research Journal, 2018)
Arabic is one of the Semitic languages: Syriac, Hebrew and Arabic. Syriac was the language of peoples whose effects and history had disappeared. Hebrew was the language of Torah and Scriptures had been extinct by the extinction of primitive cultures and ancient messages. Arabic was and is still alive with its other sisters living in the world. It is the language of an immortal divine message. God has adapted it to be the language of His Speech (Revelation) or (Qur’an), as it is stated in the verse: "We have brought down the Qur’an and we will save it". It is necessary to sanctify the eternal and miraculous language of God. As well as, it is the language of Muḥammad The prophet who brought a religion unites the hearts and souls by the love and faith, to spread peace and security in every part of the world, and presented to all of the human societies a comprehensive and universal message was the message of removal for all of the ancient religious messages. The language of this last universal message is Arabic, and its universality lies in its universal message to all people. This is the teaching of Muḥammad The prophet: "Arabic is not by the father or the mother, whoever speaks Arabic is an Arab". The classical Arabic is the language of all Arabs and Muslims who believe in its universal message. We are talking about those dialects that made up the Arabic language, as the language of the holy Qur’an.